EFEKTIVITAS CRYOTHERAPY TERHADAP TINGKAT NYERI PUNGGUNG BAWAH IBU POSTPARTUM PADA MASA PANDEMI COVID-19 - Rini Rahmayanti; Delvi Hamdayani; Fitri Wahyuni (STIKes MERCUBAKTIJAYA, 2021)
Low back pain is one of the complaints felt by some and almost all postpartum mothers since pregnancy. Low back pain occurs in 45-55% of mothers in the first week postpartum, continues at 8 weeks postpartum as much as 68% and 60% in the next 8 months. Persistent pain causes inhibition of maternal activities and reduces quality of life. One type of complementary therapy is cryotherapy cold therapy with ice. Cold therapy is a therapeutic modality that can absorb tissue temperature so that there is a decrease in tissue temperature through the conduction mechanism. The purpose of this study was to determine the effectiveness of cryoptherapy on low back pain in postpartum mothers during home care during the COVID-19 pandemic. This type of research is a pre-experimental design with One Group Pretest-Posttest with a sample of 22 early postpartum mothers (24 hours to 1 week after delivery). Data were analyzed using paired t test. The results showed that the average pain scale before being given cryotherapy was 6.82 with a standard deviation of 0.907, the average self-efficacy after being given cryotherapy was 3.96 with a standard deviation of 0.64. There was a difference in the mean value between before and after the cryotherapy intervention was given with p-value = 0.002 (p<0.05). It is hoped that health services can use cryotherapy as a therapy to reduce postpartum maternal back pain.